Kryteria oceny zobowiązania przedsiębiorcy w decyzjach Prezesa Urzędu Ochrony Konkurencji i Konsumenta w sprawach o uznanie postanowień wzorca umowy za niedozwolone wydanych w latach 2017-2023 - Monika Kuryło (Studia Administracyjne)
The study examined the criteria used by the President of the Office of Competition and Consumer Protection to evaluate commitments made by entrepreneurs during proceedings regarding the recognition of standard contractual provisions as unfair. Binding decisions issued in matters of abstract control of standard contracts differ from those issued in antitrust proceedings and in proceedings concerning practices that violate the collective interests of consumers. The discretionary nature of issuing binding decisions in matters of abstract control of standard contracts and the lack of explanations from the authority in this respect make it difficult for entrepreneurs to decide on the commitments, the content of these commitments, and how to formulate them. To identify the criteria for assessing submitted commitments, all decisions regarding the recognition of standard contractual provisions as unfair, issued between 2017 and 2023, were analyzed. The analysis shows that commitments are assessed based on the advisability of imposing them on the entrepreneur, the adequacy of the proposed actions and omissions to address the violation, the direct connection of these measures to the challenged standard provisions, and the objective and subjective completeness of the commitment, i.e., whether the proposed measures cover the effects of all disputed abusive clauses and the broadest possible group of consumers. However, the requirement that commitments be submitted at an early stage of the proceedings does not seem to align with the specificity of a binding decision issued in the case of abstract control of standard contracts. The issuance of this decision is based on proving, rather than merely substantiating, the violation of the prohibition against using unfair provisions in standard contracts. Therefore, it does not allow for shortening the proceedings before the administrative body, which should continue the evidentiary process despite the submission of the commitment.